2021
DOI: 10.1093/icvts/ivab376
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization strategies in patients with multivessel coronary artery disease: a Bayesian network meta-analysis

Abstract: Treatment modalities for multivessel disease have rapidly evolved, yet the preferred strategy remains controversial. This meta-analysis compared outcomes after on-pump (ONCAB), off-pump coronary artery bypass grafting (OPCAB), percutaneous coronary intervention (PCI) or hybrid coronary revascularization. A comprehensive search for observational studies and randomized controlled trials published by August 2020 was performed. A Bayesian network meta-analysis was conducted for early (<30 days) and late (&a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
7
1
1
Order By: Relevance
“…Another network meta-analysis compared conventional coronary artery bypass grafting (CABG) to either simultaneous or staged HCR and observed a lower rate of stroke in simultaneous HCR when compared to CABG [ 6 ]. This contrasts with the results of the randomized controlled trials, which did not observe a lower stroke rate in HCR [ 5 ]. The observational studies included in the latter meta-analysis might be influenced by residual confounding [ 6 ].…”
contrasting
confidence: 97%
See 1 more Smart Citation
“…Another network meta-analysis compared conventional coronary artery bypass grafting (CABG) to either simultaneous or staged HCR and observed a lower rate of stroke in simultaneous HCR when compared to CABG [ 6 ]. This contrasts with the results of the randomized controlled trials, which did not observe a lower stroke rate in HCR [ 5 ]. The observational studies included in the latter meta-analysis might be influenced by residual confounding [ 6 ].…”
contrasting
confidence: 97%
“…Combining the high patency of the left internal mammary artery to left anterior descending anastomosis with the less invasive nature of percutaneous coronary interventions, thereby avoiding a sternotomy, seems an attractive alternative to conventional surgery. Indeed, a recent network meta-analysis, comparing revascularization strategies and evaluating all 3 randomized trials on HCR, observed a lower need for target vessel revascularization in the long term, when compared with percutaneous coronary interventions [ 5 ]. Short-term outcomes were comparable to conventional revascularization, although the low number of patients might have led to a type II statistical error.…”
mentioning
confidence: 99%
“…In respect to postoperative MI, it is important to note that subgroup analysis consisting of RCTs found a higher risk of postoperative MI with HCR, although not significant. In contrast, Van den Eynde et al 45,59 in two separate meta‐analyses of both observational studies and RCTs found HCR to be associated with a significantly lower risk of MI both postoperatively 45 and on long‐term follow‐up 59 . Despite a relatively large study population, the authors did not conduct sensitivity analysis with only randomized trials, which typically have a more rigorous methodology compared to observational studies, and could have revealed a reliable and more accurate estimate of the risk of MI between HCR and CABG groups.…”
Section: Discussionmentioning
confidence: 88%
“…The undisputed excellent outcomes of conventional CABG utilizing internal thoracic artery (ITA) to the left anterior descending artery (LAD) and total arterial revascularization of other target vessels within various clinical scenarios and contemporary PCI technology have recently been reconfirmed . Van den Eynde and colleagues (86) recently performed a Bayesian network meta-analysis of 119 studies to compare early and late outcomes of contemporary coronary interventions in the setting of multi-vessel disease (MVD). They analysed 700,458 patients who underwent PCI (n=213,536), on-pump-CABG (P-CABG, n=438,443), off-pump-CABG (OPCABG, n=44,980) and hybrid coronary revascularization (HCR, n=3,199) with a median follow-up of 2.8 years (interquartile range, 1-5 years).…”
Section: Advances In Coronary Artery Revascularization Evidencementioning
confidence: 99%